Valiyev, Vilayat - (:unkn) unknown (My University, 2026)
Vilayet Mammad oglu Valiyev was born on March 28, 1960. In 1978, he graduated from the 49th Technical Vocational School in Sumqayit city. From 1978 to 1983, he completed his studies at the Faculty of Applied Mathematics at Azerbaijan State University (Baku State University). Between 1983 and 2003, he began his career at the Institute of Deep Oil and Gas Deposits Problems (DOGDPI) under the Azerbaijan Academy of Sciences, starting as a senior laboratory assistant. Over the years, he progressed through various positions, including engineer, senior engineer, junior research scientist, research scientist, senior research scientist, lead research scientist, chief research scientist, department head, and finally division director. After graduating from the Institute of Problems of Deep Oil and Gas Fields and the Institute of Geology under the Azerbaijan National Academy of Sciences (ANAS) in 2003, he served as the director of the Department of Economic Research of Oil and Gas Problems at the Institute of Geology until 2011 (from 2009 with substitutions). From 1985 to 1989, he pursued his postgraduate studies at the Institute of Problems of Deep Oil and Gas Fields and defended his candidate's thesis in 1990, thereby earning the degree of Candidate of Technical Sciences in the specialty of 05.15.06 - “Development and Exploitation of Oil and Gas Fields”. In 1992 and 1994, he conducted joint research at the scientific centers of UNOCAL and PENNZOIL companies in the United States, respectively. Since 1994, he has been a member of the International Association for Energy Economics (IAEE) in the United States. In 2017, he was elected as a member of the Board of Directors, and in 2018, he was selected as the Vice President for Regional Affairs. From 1995 to 1999, he pursued full-time doctoral studies at the Institute of Problems of Deep Oil and Gas Fields. In 1999, he studied and conducted joint research at the University of Oklahoma (Norman, Oklahoma, USA) on the topic of "Transition Economies Dependent on the Export of a Single Product." From 2000 to 2004, he received a second degree with honors at the Faculty of International Law of Baku State University. In 2007, he defended his dissertation at the Institute of Cybernetics of the National Academy of Sciences of Azerbaijan (the Institute of Control Systems) and earned a doctoral degree in Economic Sciences in the specialty of "Mathematical and Instrumental Methods of Economics" (code 08.00.13). In 2013, he was awarded the academic title of professor in the specialty 5302.01 - “Econometrics, Economic Statistics” (previously 08.00.13 - "Mathematical and Instrumental Methods in Economics”). In 2014, by decree of the President of the Republic of Azerbaijan, he was awarded the honorary title of "Distinguished Scientist." From 2001 to 2015, he served as a member of the Dissertation Council N.02.016 (later FD.02.016) at Baku State University, and as the chairman of the Seminar on the specialization 08.00.13 - "Mathematical and Instrumental Methods in Economics." From 2009 to 2019, he served as the Director of the Institute for Scientific Research on Economic Reforms under the Ministry of Economy of the Republic of Azerbaijan. Since the early 1990s, extensive research and service projects have been undertaken in the exploration, development, utilization, and transportation of oil and gas reserves in the region by major international oil companies such as SOCAR, BP, UNOCAL, PENNZOIL, and others. These projects cover a wide range of issues including technical-economic and commercial assessments, prospective development plans and forecasts, the creation of information databases, and the development of decision-making mechanisms and models. Since the early 2000s, he has been involved as a leader and principal executor of local and international projects aimed at addressing issues of energy and socio-economic development. These projects have been supported by the World Bank (WB), the European Bank for Reconstruction and Development (EBRD), the Asian Development Bank (ADB), the United States Agency for International Development (USAID), the European Union (EU), the German Corporation for International Cooperation (GIZ), the Turkish Cooperation and Coordination Agency (TIKA), the Economic Cooperation Organization (ECO), and other international financial institutions, economic, and regional organizations. His contributions include energy policy and regulation, modeling of socio-economic development, strategic planning and forecasting, as well as fostering university-industry collaboration and other aspects of innovative development, successfully implementing numerous projects in these fields. Since 2012, Vilayet Valiyev has been serving as an associate professor at the Azerbaijan National Aviation Academy. He is the author of 112 scientific works, including more than 40 published abroad, as well as one monograph and one textbook.